Cerebellar Malformations and Cognitive Disdorders - J Gordon Millichap (Pediatric Neurology Briefs)
The behavioral developmental profile of 27 children and adults (17 males and 10 females) with congenital cerebellar malformations was determined in a clinical, neuroradiological and neuropsychological study at the Scientific Institute 'E Medea', University of Milano, Italy.